Evaluation of the Effectiveness of Learning Management in University - Mesta Limbong (Institut Agama Islam Negeri (IAIN) Curup, 2023)
This study aims to obtain scientific information about the achievement and effectiveness of curriculum management in tertiary institutions. The research method used is evaluative research. Data collection uses techniques with field observations by looking directly at and observing sources directly with observation sheets in obtaining data. Data was also obtained by interview. Some of the sources were interviewed to ensure the correctness of the data during observation. Then the data is also obtained with instruments that are shared to view secondary data, and finally, to collect supporting document data. Methods of data analysis using descriptive quantitative and qualitative methods. The results obtained from the evaluation results obtained the value of each aspect, namely: 1) functionalization of learning curriculum management in tertiary institutions, namely 75.46 and is in the good category, 2) management of curriculum management is worth 100 and is in the very good category, 3) management students score 80 and in the good category. This has a positive impact on the development of educational management in the future.